2014
DOI: 10.1111/jbfa.12098
|View full text |Cite
|
Sign up to set email alerts
|

Does Limited Attention Constrain Investors’ Acquisition of Firm‐specific Information?

Abstract: According to the framework outlined in Peng and Xiong (), attention‐constrained investors tend to process more market‐ and sector‐level information. We empirically test this theory. We find that firms with higher media coverage have lower contemporaneous stock return synchronicity. Such an effect is robust to analyses within size deciles, inclusion of firm fixed effects, estimation using a matched sample, and a two‐stage least squares approach. The effect becomes less pronounced during the financial crisis per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
(162 reference statements)
1
10
0
Order By: Relevance
“…Since Roll (1988), a considerable amount of research has identified links between comovement and investor protection and development of financial market, corporate governance, mandatory adoption of XBRL and newspaper coverage (Morck et al, 2000;Durnev et al, 2003;Crawford et al, 2012;Dong and Ni, 2014;Dong et al, 2016). Our study points to the role of social media in influencing stock return co-movement.…”
Section: Introductionmentioning
confidence: 67%
“…Since Roll (1988), a considerable amount of research has identified links between comovement and investor protection and development of financial market, corporate governance, mandatory adoption of XBRL and newspaper coverage (Morck et al, 2000;Durnev et al, 2003;Crawford et al, 2012;Dong and Ni, 2014;Dong et al, 2016). Our study points to the role of social media in influencing stock return co-movement.…”
Section: Introductionmentioning
confidence: 67%
“…To use an instrumental variable that is correlated with media coverage of industry but unrelated to stock return, the average IAT value of other industries that share the same first-level industry classification with the stock is selected. Dong and Ni (2014) document that a firm is more likely to seek media coverage when more peer firms appear in the media, furthermore, because the instrumental variable and the original industry are under the same first-level industry classification, they should share common shocks, fundamentals, information, and policies. Based on this understanding, this instrumental variable is likely to satisfy the relevance requirement.…”
Section: Two-stage Least Squares (2sls) Regressionmentioning
confidence: 99%
“…Merton (1987) advanced the investor recognition hypothesis, and revealed that stocks with little media coverage are less recognised by investors, and therefore, they should offer higher equity premiums than these with good investor recognition, as a compensation of their holders for suffering from information asymmetry. This perspective is supported by numerous empirical studies that high media coverage has a negative impact on return in the short term, but this tendency reverses eventually (e.g., Chan, 2003; Chen et al ., 2014; Dong and Ni, 2014; Fang and Peress, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we find that voluntary corporate disclosures have an incremental effect to media coverage, leading to 2 For example, Rogers, Skinner, and Zechman (2016) examine the disseminating role of the media and provide evidence that the financial press plays a significant role in price formation in capital markets through the wide dissemination of news. Acknowledging that investors are attention-constrained, Dong and Ni (2014) use stock return synchronicity as a proxy for the proportion of firm-specific information in stock prices, and find that firms with higher media coverage have less synchronous stock returns.…”
Section: Introductionmentioning
confidence: 99%